Pupillary Measures of the Cognitive Effort in Auditory Novel Word Processing and Short-Term Retention - López-Ornat, Susana; Karousou, Alexandra; Gallego, Carlos; Martín, Leire; Camero, Raquel (Frontiers in Psychology, 2018)
The use of the task-evoked pupillary responses (TEPRs) methodology is emerging in the psycholinguistics literature, as a sensitive, reliable and dynamic psychophysiological measure of the cognitive effort produced by various aspects of language processing. This preliminary study aimed to assess the functionality and effectiveness of a TEPRs design for measuring the cognitive effort required for the processing and spontaneous (non-explicitly prompted) short-term retention of novel phonological forms presented auditorily. Twenty-four young adult participants (aged 19-28 years, M= 20.3, SD= 2.13) were auditorily presented with a series of pseudowords differing in their number of syllables and their syllabic complexity. Then, they were asked to produce a response to a delayed pseudoword–color matching task aimed to induce the short-term retention of the novel forms. Results on the size and timing of the TEPRs reveal a significant pupillary activation, starting immediately after the presentation of the auditory stimuli, peaking at 1080ms and not subsiding significally during the protracted retention period. Moreover, the differential complexity of the novel words phonology significantly affected pupillary activation. Overall, these preliminary results point to the effectiveness of pupillometry as a technique for capturing the cognitive effort entailed in the short-term maintenance of novel word forms in the phonological loop, a process deemed crucial in the everyday novel word learning process. Results are discussed in view of future research that could establish and extend their implications.